Pneumococcal serotypes and their association with death risk in invasive pneumococcal disease: a systematic review and meta-analysis - Darkwah, Samuel; Somda, Namwin S.; Mahazu, Samiratu; Donkor, Eric S. (Frontiers in Medicine, 2025)
BackgroundStreptococcus pneumoniae and its infections are a global public health concern. Invasive pneumococcal disease accounts for significant mortality in the aged and immunocompromised. Over 100 unique capsular serotypes have been identified, with 80–90% of invasive disease attributable to about 23 serotypes. Pneumococcal serotype influences invasiveness, virulence, carriage, and IPD outcome. Case fatality rates among different pneumococcal serotypes in IPD have been inconsistently reported, prompting the need for a comprehensive meta-analysis. We hypothesized that specific pneumococcal serotypes would be associated with higher case fatality rates and that non-vaccine serotypes may exhibit increased mortality risks over time.MethodsWe conducted a systematic review and meta-analysis of serotype-specific risk of death due to invasive pneumococcal disease (IPD) in the last decade. We calculated the risk ratio (RR) and 95% confidence interval (CI) for each serotype compared with serotype 14 in each study. Pooled risk ratios were computed using random effects size model analysis. We also conducted heterogeneity testing and meta-regression sub-analysis.ResultsIn total, 45 eligible studies were included, and 16 were selected for meta-analysis. Study distribution showed a global disparity, with Europe as the major data source. Serotype 31 had the highest case fatality rate (31.4%), indicating a concerning mortality risk associated with this serotype, particularly in immunocompromised patients. Overall, IPD patients with serotypes 3, 6A, 11A, 15A, 19F, and 31 were more likely to die. In contrast, serotypes 1, 5, 7F, and 8 IPD isolates recorded a reduced risk ratio compared to serotype 14. Subgroup analysis showed that vaccine serotypes were associated with a greater risk of death than non-vaccine serotypes, but there were no significant differences in risk estimates between population groups.ConclusionThe study confirms the stable role of pneumococcal serotype in determining the clinical outcomes of invasive pneumococcal disease. Our findings underscore the importance of serotype-specific surveillance in IPD and call for the reconsideration of current pneumococcal vaccine formulations to address high-risk non-vaccine serotypes. Efforts to build research capacity, especially in low-resource regions such as Africa and South America, are highly recommended.